Geotechnical risk management at Teck Coal - Bidwell, A; Knight, A; Anderson, WS (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
The first standardised Geotechnical Assessment Process for identifying and assessing geotechnical risks at Teck Coal’s open pit mining operations was developed and implemented in 2012. This work was started as a corporate initiative because Teck, as a publicly traded company, desired to demonstrate industry-best practices for managing geotechnical risks and to develop Teck Coal corporate geotechnical standards. Furthermore, corporate geotechnical standards and a consistently high level of geotechnical practice are required as part of the safe and profitable execution of the potential expansions at Teck Coal’s operating sites and the possible development of additional mines. This paper describes the three stage Geotechnical Assessment Process – the application of an assessment tool to scrutinise the geotechnical aspects of mine design, operation and closure, the categorisation and ranking of identified geotechnical risks, and the development of action plans to mitigate the risks. The assessment tool was developed in-house because there were no suitable published or publicly-available procedures. The risk categorisation and ranking procedure was adapted from the existing Teck stage gating process used for major projects. The ranked risks were grouped by common themes, and then used as the basis for developing site-specific ‘Project Initiatives’ that list actionable steps to ensure that each site’s geotechnical systems and processes are aligned with Teck Coal’s emerging standardised approach for identifying and managing the geotechnical risks at existing operations and for potential expansions.